Exports in a Tariff-Free Environment : What Structural Reforms Matter? Evidence from the European Union Single Market - Rahman, Jesmin (IMF Working Papers; Working Paper ;, 2015)
How do countries enhance their exports of goods in a largely tariff-free environment? Our investigation of export performance of new member states in the European Union single market, which provides a natural control for barrier-free environment, points to the importance of structural reforms, particularly in the areas of higher education, skills upgrade, wage structure's ability to provide incentives to work and foreign investment environment. In addition, establishing links with supply chains, which in addition to the above-mentioned reforms also depend on better institutions and infrastructure, are important. The analysis in the paper shows that new member states are at varying levels of quality and integration, which highlights the need for country-specific policy priorities. Services trade, which is subject to significant non-tariff barriers in the EU market even after the implementation of the Services Directive, shows considerable room for growth given the comparative advantage of some of the new member states.